Systematic review with meta‐analysis: The effect of vitamin E supplementation in adult patients with non‐alcoholic fatty liver disease. Issue 2 (10th September 2020) - Vadarlis, Andreas; Antza, Christina; Bakaloudi, Dimitra Rafailia; Doundoulakis, Ioannis; Kalopitas, Georgios; Samara, Myrto; Dardavessis, Theodoros; Maris, Theofanis; Chourdakis, Michail
Abstract: Background and Aim: Νon‐alcoholic fatty liver disease (NAFLD) is estimated to be the most common cause of end‐stage liver disease in the next years. Vitamin E has shown beneficial effects as a possible "scavenger" of oxidative stress products, which play a major role in pathogenesis of the disease. The purpose of the present meta‐analysis is to investigate the effects of vitamin E supplementation in biochemical and histological parameters in adult patients with NAFLD. Methods: Literature search was performed in major electronic databases (MEDLINE, CENTRAL, and Embase) up to June 2020 for randomized clinical trials, which examined vitamin E versus placebo treatment in adults with NAFLD. Changes in liver enzymes were considered as primary outcomes while changes in histological, biochemical, and metabolic parameters as secondary. Quality of evidence was assessed through risk of bias according to the Cochrane risk of bias tool. Results: Eight studies were included in qualitative analysis and seven in quantitative analysis. Vitamin E reduced the values of liver enzymes compared with placebo (−7.37 IU/L, 95% confidence interval: −10.11 to −4.64 for alanine aminotransferase, and −5.71 IU/L, 95% confidence interval: −9.49 to −1.93 for aspartate aminotransferase). Additionally, vitamin E improved statistically significantly liver pathology in every individual histological parameter as well as low‐density lipoprotein cholesterol, fasting blood glucose, and serum leptin values. Conclusions: Vitamin E can improve biochemical and histological characteristics of NAFLD patients, especially of non‐alcoholic steatohepatitis patients. The results indicate that vitamin E could be a promising choice and be considered as a treatment option in patients with NAFLD.